Moderasi Beragama dalam Pendidikan Anak Usia Dini (PAUD/TK): Konsep, Tantangan, dan Strategi Implementasi - Nur Hasana Alvi Syahrin; Nurul Hadidah Al-Hadid; Ziha Fida Utami Tanjung; Masganti Sit (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Religious moderation is a fundamental concept in maintaining social harmony within a multicultural society such as Indonesia, and early childhood education represents a strategic stage for instilling values of tolerance, inclusivity, and respect for diversity. This article aims to analyze the concept of religious moderation, identify challenges in its implementation, and formulate strategies for strengthening religious moderation in early childhood education. The study employs a descriptive qualitative method using a literature-based integrative review approach, analyzing 15 sources consisting of national and international journal articles, academic books, and official government policy documents. The findings indicate that religious moderation in early childhood education can be effectively implemented through thematic learning integration, teacher role modeling, inclusive school culture, and collaboration among schools, parents, and the wider community. However, several challenges persist, including limited teacher understanding, insufficient continuous training, the influence of social media, and resistance from local cultural norms. The originality of this article lies in its comprehensive synthesis of conceptual and practical perspectives on religious moderation that specifically focuses on early childhood education by linking Indonesia’s national policy framework with global multicultural and citizenship education discourse. The study concludes that strengthening religious moderation from an early age requires collaborative strategies, curriculum reinforcement, and sustained capacity building for educators to foster tolerant character development and prepare children to engage constructively with global diversity